Analisis Ilokusi dan Implikaturnya pada Teks Iklan, Slogan, dan Poster dalam Materi Bahasa Indonesia Kelas VIII Kurikulum Merdeka - Amelia Novitasari; Monica Zahroh; Zidna Fitriana; Ergita Amiarti; Jihan Malika Utami; Asep Purwo Yudi Utomo; Amilia Buana Dewi Islamy (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to analyze illocutionary and implicatures in advertisments, slogans, and posters in the Indonesian language material for class VIII Merdeka Curriculum. This research uses a descriptive qualitative and pragmatic approach. The authors obtained data by listening and reading related references and recording information that could be used a data. For this reason, the techniques used in this research are listening, reading, and note-taking. The data studied in this research are advertisments, slogans, and posters in the Indonesian language material for class VIII Merdeka Curriculum. The data analysis method used in this article method and pragmatic heuristic method. Researchers analyzed the text in depth in terms of characteristics and truth testing. As a result of data analysis, only three types of five types of illocutionary speech acts were found in the 12 samples on advertisment images, slogans, and posters, including (1) assertive speech acts of stating and providing information; (2) inviting directive speech acts; and (3) prohibit declarative speech acts. Through this research, it is hoped that we will be able to obtain an overview of illocutionary speech acts and their implicatures found in advertisments, slogans, and posters and practically this research can be used as a basis for future researchers, especially regarding the analysis of illocutionary speech acts and their implicatures.